Application of dietary fibers as value addition in dairy and food industry - suvera, priyanka ajitbhai (Indian Journal of Dairy Science, 2017)
Dietary fiber (DF) is a carbohydrate polymer, which are neither digested nor absorbed in the small intestine. Fiber is found in varying quantities in all plant foods. DF can be classified into two groups based on their sources: water-soluble and water insoluble fibers. Fibers have certain technical and nutritional functionality, which correlated to texture of food and health of consumer respectively. It improves the sensory characteristics, texture and shelf life of foods due to their water-binding capacity, gel-forming ability, fat mimetic, anti-sticking, anti-clumping, texturising and thickening effects. DF have been used to reduce theÂ Â blood cholesterol, post prandial blood glucose, intestinal transits time and enhance the immune function, fermentability, stool bulk, production of SCFAS (short chain fatty acids). DF is widely fortified in dairy and food products such as baked goods, ice cream, cheese, beverages, yoghurt, jam, marmalades, pasta, tortilla, meat, fish, chocolate etc. Now, it is need to supplement DF into various new dairy/food products with better functional and therapeutic properties